2010
DOI: 10.1007/s00540-010-0950-1
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Pentax-AWS Airwayscope utility as an intubation device during cardiopulmonary resuscitation on the ground

Abstract: We conclude that the AWS is an effective device for endotracheal intubation during chest compression not only on the bed but also on the ground.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
3

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 26 publications
0
27
0
3
Order By: Relevance
“…9 Moreover, overall success rates were significantly lower with the Macintosh laryngoscope than with the Pentax-AWS. 7,8,10 Success rates of 100% have been reported for the Pentax-AWS compared with success rates of 57.1%, 8 74.3%, 10 and 81.3% 7 reported for the Macintosh. 8 In the present study, the overall success rate for the Macintosh laryngoscope was similar to that of the Pentax-AWS in a normal airway scenario (96.9% vs 100%, respectively).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…9 Moreover, overall success rates were significantly lower with the Macintosh laryngoscope than with the Pentax-AWS. 7,8,10 Success rates of 100% have been reported for the Pentax-AWS compared with success rates of 57.1%, 8 74.3%, 10 and 81.3% 7 reported for the Macintosh. 8 In the present study, the overall success rate for the Macintosh laryngoscope was similar to that of the Pentax-AWS in a normal airway scenario (96.9% vs 100%, respectively).…”
Section: Discussionmentioning
confidence: 97%
“…[7][8][9][10][14][15][16] The laryngoscopes employed in the majority of these previous studies were the conventional Macintosh laryngoscope and the Pentax-AWS. [7][8][9][10]14,15 While four studies [7][8][9][10] reported that the Pentax-AWS was more effective than the Macintosh laryngoscope, two studies 14,15 reported no significant difference.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors mentioned that the operator skills based on an adequate amount of experience would influence their results. However, Komasawa et al 8 proposed that the AWS requires less operator skill. Considering these past findings, it appears that the AWS will be useful to achieve successful tracheal intubation during chest compression compared to MCL even if the operator is a novice.…”
Section: Discussionmentioning
confidence: 99%